Cotidiano, demandas e apoio social de famílias de crianças e adolescentes com autismo - Minatel, Martha Morais (Universidade Federal de São Carlos, 2013)
In each development phase of an individual suffering from a disability, different demands and challenges arise to the families and professionals involved in this reality. This study has aimed on identifying, through the standpoint of the families of autistic infants and teenagers, their daily experiences, demands, as well as the perceived social support while facing the reality of the care given to their children during three development phases. Twenty families of infants and teenagers with autism diagnostics have participated of this study, organized into three groups: Group 01 (with autistic children from 3 to 6 years old); Group 02 (with autistic children from 7 to 11 years old), and Group 03 (with autistic children from 12 to 18 years old). In order to gather data, there have been used semi structured interview routines, and Identification Questionnaires. Amongst the main results, there have been identified that the daily routine of the participant families is organized according to the autistic family members, their needs, and their difficulties. Such aspect has been observed within the domestic environment as well as in the external activities. Some of the identified difficulties are shared by all the studied groups, such as some of the daily routine difficulties, the ones in social activities, in the communication with these children, their dependency with their personal hygiene, among others. Specifically in each phase, the results of Group 01 have highlighted the families difficulties regarding the acceptance of the diagnostic, in Group 02 stands out the behavioral difficulties and the prejudice with this condition, and, in Group 03, the difficulties regarding adolescence specific issues, particularly the ones regarding the teenagers physiological development. Concerns with the children s future are perceived in all three groups, particularly the concern regarding who would take care of the children when the parents are not around anymore, which increases in intensity as the years pass by. In relation to the social support perceived by the main care givers, the family, their partners, siblings and grandparents of the individual with autism have been identified as the main sources. Besides that, some strategies for facing their problems have been identified in many situations of the families daily routine, where arrangements and possibilities are willful explored. There have been identified with the family members some demands for guidance in relation to the children s development, in how to help these individuals with their condition and with other subjects. In conclusion, this study have achieved its goals contributing for enlarging the knowledge in this area, providing benefits for future researches, actions and interventions planning for this population, as well as supporting planning public policies.
Keywords: Terapia ocupacional; Autismo; Família; Apoio social; Cotidiano; Autism; Family; Social support; Occupational therapy; Everyday; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL